Energy Efficiency in India's Iron and Steel Industry: A Firm-level Data Envelopment Analysis. Issue 3 (1st January 2019) - Ohlan, Ramphul
ABSTRACT: India's national mission to improve energy efficiency focuses on enhancing the efficiency in its most energy-intensive industries. Motivated by this mission, we measure and analyze energy efficiency in the country's iron and steel industries applying data envelopment analysis using firm-level panel data over the period 2004-2012. The results show that the energy efficiency of India's iron and steel industries has improved and energy intensity has declined during the study period. However, there is a large potential for these industries to further reduce energy use. The results of the regression analysis obtained using panel data indicate that larger firms tend to have higher energy efficiency. In addition, labor productivity improves energy use efficiency. Improvements in energy efficiency, particularly in small and medium firms should be encouraged.